HUBUNGAN SUMBER INFORMASI DENGAN PERSEPSI REMAJAKELAS XI TENTANG KEHAMILAN REMAJADI SMAN 1 GONDANG-MOJOKERTO - Purwati, Heni; Sajidin, M. (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The development of information which is able to become the stimulus in influencing of someone perception, especially the teenagers who are in their growing of having many questions in their life, they always want to know and also want to try it. This research was to know whether the correlation between information source and teenager perception XI grade about adolescence pregnancy at SMAN 1 Gondang Mojokerto. The research design was analytical correlation with cross sectional approaching. The research population were all of the students XI grade, they were 208 teenagers. The sampling technique was probability cluster random sampling by having 137 sample. The technique of gathering data was questionare. The research had been done on August 7th, 2014. The result of the research was most of the teenager XI grade accesed the information source of electronic media, they were 112 respondences (82%) and teenager perception XI grade about adolescence pregnancy most of their perceptions were negative which have 70 respondences (51%). The getting data was counted by using statistic test the coefisien contingency was p=0,352 (>0,05) it meant that H0was accepted whereas H1was rejected, which was also meant that there is no correlation between the correlation of information source and teenager perception XI grade about adolescence pregnancy. On the other sourch, the teacher should be the main information source for teenagers because the information which is explained by the teacher is a valuable and educated information, so if the teenagers get valuable information, they will have positif perception.Key words: information source, perception, adolescence pregnancy.